Faouzi Laatiris : fugues chimériques dans la mondialisation - Morad Montazami (Revue des Mondes Musulmans et de la Méditerranée)
Faouzi Laatiris, a fairly unclassifiable and marginal artist, opened the way for his work to be studied, more in depth, quite recently. Such task can be led only provided a clear view of the context where his practice developed, at the Institut national des beaux-arts in Tetouan, where he teaches since 1993, and still to this day. How can one relocate this key figure of globalized contemporary art, taking Morocco as a starting point but extending him to a transcultural art history, both local and global (both European and Arab, both North African and African more generally, eventually Mediterranean)? Torn between his interest for Western modern art and his intimate relation to the Moroccan land, its traditions and vernacular knowledge, he ends up constructing objects and installations demonstrating – as he puts it himself –a kind of “cultural schizophrenia”. Installation art based on principle of permanent variation and permutation of forms, as if the artwork “escaped” us. Or as if it escaped from archives and documentation, as it tends to improve a sense of rarity; an artwork that refuses to withdraw into itself or to take a irrevocable shape.